Case Report: Presence of Anti-MAG in the CSF Can Be Associated With a Neurodegenerative Process With Frontal Involvement - Dorcet, Guillaume; Benaiteau, Marie; Ory-Magne, Fabienne; Blancher, Antoine; Pariente, Jérémie; Fortenfant, Françoise; Bost, Chloé (Frontiers in Neurology, 2022)
BACKGROUND: Autoimmune encephalitis (AIE) is an increasingly broad nosological framework that may clinically mimic neurodegenerative diseases (NDD). CASES REPORTED: We describe here the clinical, radiological, electrophysiological and biological evolution of three patients. Two females aged 73 and 72 years and a 69-year-old male presented with complex cognitive and focal neurological symptoms having in common a predominant frontal dysexecutive involvement and an unexpectedly high titer of anti-MAG antibodies in the serum and cerebrospinal fluid (CSF). The question of an autoimmune cause was raised. After two years of follow-up and, for two of them, without improvement despite immunosuppressive treatments, diagnoses of NDD were eventually retained: post-radiation encephalopathy, progressive supranuclear palsy (PSP) and Alzheimer’s disease (AD). CONCLUSION: The presence of a high titer of anti-MAG antibodies may be found in NDD. It could reflect cerebral tissue damages, particularly in case of significant frontal involvement. Atypical presentations may lead to a search for a paraneoplastic neurologic syndrome or AIE. However, the indirect immunofluorescence staining positivity on monkey cerebellum section linked with anti-MAG antibodies should not lead to those diagnoses being retained.